TGF-β/Smad3 Signaling Regulates Brown Adipocyte Induction in White Adipose Tissue - Rane, Sushil G.; Yadav, Hariom (Frontiers in Endocrinology, 2012)
Recent identification of active brown fat reserves in adult humans has stimulated interest in the role of brown adipocytes in energy homeostasis. In addition, there is accumulating evidence to support the concept of an alteration in energy balance through acquisition of brown fat features in traditional white fat depots. We recently described an important role played by the TGF-beta/Smad3 signaling pathway in modulating the appearance of brown adipocytes in traditional white fat, and its implications to thermogenesis, mitochondrial energetics, energy expenditure and protection from diabetes and obesity. Here we review the data supporting this phenomenon and put into perspective the promise of conversion of white fat to a brown fat state as a potential therapeutic option for obesity and diabetes.